IgE recognition of chimeric isoforms of the honeybee (Apis mellifera) venom allergen Api m 10 evaluated by protein array technology. Issue 2 (February 2015) - Van Vaerenbergh, Matthias; De Smet, Lina; Rafei-Shamsabadi, David; Blank, Simon; Spillner, Edzard; Ebo, Didier G.; Devreese, Bart; Jakob, Thilo; de Graaf, Dirk C.
Highlights Nine additional Api m 10 transcript isoforms are discovered. The previously known variant 2 is produced by an alternative splicing event. Novel identified isoforms are intragenic chimeric transcripts. IgE recognition of Api m 10 is both isoform- and patient-specific.